Influence of capping agents on physicochemical properties and leukemic cytotoxicity of copper oxide nanoparticles biosynthesized using Caesalpinia sappan extract - Mathurada Sasarom; Songyot Anuchapreeda; Wim E. Hennink; Siriporn Okonogi (PLoS ONE, 2025)
The aim of this study was to investigate the effects of capping agents on the physicochemical and biological properties, particularly their leukemic cytotoxicity, of copper oxide nanoparticles (CuONPs) using a Caesalpinia sappan extract as a reducing agent. Gelatin, polyethylene glycol 400 (PEG), polysorbate 80 (P80), octyl phenol ethoxylate, sodium lauryl ether sulfate and mannitol were added as capping agents to ensure colloidal stability of the formed CuONPs. As a control, CuONPs were also synthesized using gelatin and sodium borohydride as the capping and reducing agent, respectively. The physicochemical properties of the obtained CuONPs were determined using dynamic light scattering, zeta-potential measurements, energy dispersive X-ray spectroscopy, and Fourier-transform infrared spectroscopy. Their cytotoxic effects were investigated using normal human peripheral blood mononuclear cells (PBMC) and three strains of leukemic cell lines (KG1a, K562, and Molt4). The obtained CuONPs had a size range from 175–280 nm, with a reasonable size distribution between 0.2 and 0.4 and a negative zeta potential (range −30 to −35 mV) except the particles prepared using gelatin as a stabilizer which had a zeta potential of −3 mV. The CuONPs were incubated with both healthy PBMC and three types of leukemic cells to determine their IC50 values. The IC50 values of PEG-CuONPs and P80-CuONPs against healthy PBMC were 72.5 ± 5.8 and 85.0 ± 3.1 µg/mL, respectively, while that against the three strains of leukemic cells were in the range of 26–29 and 28–41 µg/mL, respectively. The results clearly demonstrate that the biosynthesized CuONPs using PEG and P80 as a capping agent exhibited the highest selectivity index defined as IC50 of the particles for PBMC/IC50 for leukemic cells. Therefore, these CuONPs are promising candidates for preclinical in vivo for leukemic treatments.